ANALISIS KESALAHAN PENGGUNAAN HURUF KAPITAL DAN TANDA BACA PADA SURAT KELUAR DI KANTOR DESA ORAHILI FONDRAKO KECAMATAN ULUSUSUA TAHUN 2022 - Halawa, Katarina Aperida (Universitas Nias Raya, 2024)
The problem with this research is that there are still many problems with capital letters and punctuation in outgoing letters at the Orahili Fondrako village office, Ulususua District. This is supported by initial observations made by researchers. The aims of this research are 1) to describe capital letter errors and 2) to describe punctuation errors in outgoing letters at the Orahili Fondrako village office in 2022. The research method used is qualitative and descriptive. The data collection technique used is documentation. The data source for this research is letters distributed at the Orahili Fondrako village office. Based on the research results, the researcher drew the following conclusions: (,) and period (.). In the Orahili Fondrako Village office, Ulususua District, errors occur due to lack of writing skills, limited dominance of language rules and inaccuracies in writing outgoing letters, therefore it is necessary to be alert to errors in the use of punctuation marks used and correct them when writing letters. This shows that there is an error in using comma punctuation marks such as 2 (two) and 4 (two). four) types of errors in using punctuation 6. Recommendations that can be given include: 1) continuing the use of spelling by educational practitioners, 2) other researchers should conduct further research on this matter. Bluedan 3) Errors are reserved for the teacher, so that students continue to be taught the correct and correct use of spelling.